Collected Papers from Past Texas Archeological Society Summer Field Schools - Perttula, Timothy K. (Texas Archeological Society, 2008)
Series of articles documenting four Texas Archeological Society Field Schools, describing each of the projects including the environment, cultural context, and archaeological findings.